Prostate-Specific Antigen (PSA) as a Predictor of Prostate Cancer on Transrectal Biopsy: A Meta-Analysis - Arief Aulia; Hafiz Mirza Fadrian (Open Access Indonesian Journal of Medical Reviews, 2024)
Prostate cancer is a leading cause of cancer-related death in men globally. Early detection is critical for improving patient outcomes. Prostate-specific antigen (PSA) testing is a widely used screening tool, but its accuracy in predicting prostate cancer on transrectal biopsy remains a topic of debate. This meta-analysis aims to evaluate the diagnostic accuracy of PSA in predicting prostate cancer on transrectal biopsy. A systematic search of electronic databases (PubMed, Scopus, Web of Science) was conducted to identify relevant studies published between 2013 and 2024. Studies reporting the sensitivity, specificity, and area under the receiver operating characteristic curve (AUC) of PSA for predicting prostate cancer on transrectal biopsy were included. Data were extracted, and the pooled sensitivity, specificity, positive likelihood ratio (PLR), negative likelihood ratio (NLR), and diagnostic odds ratio (DOR) were calculated using a random-effects model. Six studies met the inclusion criteria, comprising a total of 1,245 patients. The pooled sensitivity and specificity of PSA for predicting prostate cancer on transrectal biopsy were 0.77 (95% CI, 0.75 - 0.82) and 0.68 (95% CI, 0.62-0.73), respectively. The pooled PLR, NLR, and DOR were 3.27 (95% CI, 2.45-4.37), 0.20 (95% CI, 0.14-0.28), and 16.39 (95% CI, 10.27-26.21), respectively. The pooled AUC was 0.87 (95% CI, 0.84-0.90). In conclusion, PSA demonstrates good diagnostic accuracy in predicting prostate cancer on transrectal biopsy. However, it is essential to consider its limitations, including false positives and negatives. Further research is needed to identify strategies to improve the accuracy of PSA testing and reduce unnecessary biopsies.